2021
DOI: 10.1007/s42761-021-00036-y
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Naming Impedes Both Cognitive Reappraisal and Mindful Acceptance Strategies of Emotion Regulation

Abstract: Friends and therapists often encourage people in distress to say how they feel (i.e., name their emotions) with the hope that identifying their emotions will help them cope. Although lay and some psychological theories posit that emotion naming should facilitate subsequent emotion regulation, there is little research directly testing this question. Here, we report on two experimental studies that test how naming the emotions evoked by aversive images impacts subsequent regulation of those emotions. In study 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Studies that examine mindful attention as an emotion regulation strategy have shown that it can reduce negative affect (Nook et al, 2021;Westbrook et al, 2013), pain (Kober et al, 2019), and nicotine cravings (Westbrook et al, 2013). These studies also indicate that mindful attention is an effective emotion regulation strategy for individuals who do not practice meditation (Kober et al, 2019;Nook et al, 2021;Westbrook et al, 2013), highlighting its potential utility as an intervention target in everyday life. In the context of substance use, both trait mindfulness (Karyadi et al, 2014) and mindfulness training (Brewer et al, 2012;Tapper, 2018;Westbrook et al, 2013) have been associated with decreased cravings for food, alcohol, and smoking, and various mindfulness-based interventions have been developed to reduce substance use (Chiesa & Serretti, 2014;Goldberg et al, 2022;Li et al, 2017).…”
Section: Mindful Attentionmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies that examine mindful attention as an emotion regulation strategy have shown that it can reduce negative affect (Nook et al, 2021;Westbrook et al, 2013), pain (Kober et al, 2019), and nicotine cravings (Westbrook et al, 2013). These studies also indicate that mindful attention is an effective emotion regulation strategy for individuals who do not practice meditation (Kober et al, 2019;Nook et al, 2021;Westbrook et al, 2013), highlighting its potential utility as an intervention target in everyday life. In the context of substance use, both trait mindfulness (Karyadi et al, 2014) and mindfulness training (Brewer et al, 2012;Tapper, 2018;Westbrook et al, 2013) have been associated with decreased cravings for food, alcohol, and smoking, and various mindfulness-based interventions have been developed to reduce substance use (Chiesa & Serretti, 2014;Goldberg et al, 2022;Li et al, 2017).…”
Section: Mindful Attentionmentioning
confidence: 89%
“…Mindful attention is thought to facilitate psychological distancing through "defusion" or "decentering" from one's emotional experience (Kang et al, 2013). Studies that examine mindful attention as an emotion regulation strategy have shown that it can reduce negative affect (Nook et al, 2021;Westbrook et al, 2013), pain (Kober et al, 2019), and nicotine cravings (Westbrook et al, 2013). These studies also indicate that mindful attention is an effective emotion regulation strategy for individuals who do not practice meditation (Kober et al, 2019;Nook et al, 2021;Westbrook et al, 2013), highlighting its potential utility as an intervention target in everyday life.…”
Section: Mindful Attentionmentioning
confidence: 99%
“…These lines of data suggest that applying specific emotion language should facilitate later regulation. However, tight empirical investigations have actually found the opposite: Labeling emotions makes subsequent regulation less effective (Nook et al, 2021b), and labeling emotions using many emotion words leads people to select more maladaptive regulatory strategies than if they had used just a few emotion words (Vine et al, 2019). There are certainly ways to iron out the logic to make these findings fit (e.g., perhaps precise labeling boosts regulation at longer time horizons than these experiments tested?…”
Section: Clarifying Mechanisms and Developing Causal Modelsmentioning
confidence: 91%
“…Conversely, emotion differentiation might actually explain why vocabulary is associated with mental health (i.e., people with larger vocabularies can use more specific terms to label their emotions, boosting regulation and ultimately mental health). This distinction becomes especially interesting in a developmental context, where language may contribute to growths in emotion conceptualization (Nook et al, 2017;Hoemann et al, 2019Hoemann et al, , 2020bNook and Somerville, 2019). Similarly, as hinted above, mean negative affect may confound the relationship between differentiation and health, or it may mediate this relationship.…”
Section: Ruling Out Third Variablesmentioning
confidence: 94%
See 1 more Smart Citation